EFFECTIVENESS OF DISCOVERY LEARNING MODEL ASSISTED BY VBA FOR EXCEL TO IMPROVE THE COMPREHENSION ABILITY OF GRADE IV ELEMENTARY SCHOOL STUDENTS - Chotimah, Siti; Rosyana, Tina; Bernard, Martin (Kopertis Region IV Jabar and Banten, 2024)
This research is motivated by students' difficulties in solving story problems on the material of area and perimeter of flat shapes, therefore a learning model and interactive media are needed to overcome these problems. The alternative learning model applied is the discovery learning model. And the media used to help the learning process of VBA for Excel students. The purpose of this study was to examine the improvement of students' understanding ability in one of the State Elementary Schools in Bandung Regency. The instrument used in this research is a description question with as many as four items to determine students' understanding ability. The research method used in this research is experimental in the form of a group pretest-posttest design. The subjects in this study were students in one of the public elementary schools in Bandung Regency. The research data were obtained from the pretest and posttest results. The data were then processed using IBM SPSS Statistics 25 software. The results of data processing showed that there was an increase in the understanding ability of elementary school students after being given treatment using the discovery learning model assisted by VBA for Excel. Students are very enthusiastic about learning, it is proven that the discovery learning model assisted by VBA for Excel is very effective for further learning.